Filosofía y método: vías de contemplación en Plotino - Hermoso Félix, María Jesús (2025)
This paper explores Plotinus’ methodological approach considering the practical perspective of his philosophy. According to Plotinus, there is something in us that is permanently oriented towards the intelligible realm (En. IV 8. 8. 5). Contemplation is a continual activity for the soul. We do not cease to contemplate; our being and our individuality depend on it. However, this activity often goes unnoticed (En. I 1. 11. 9). The possibility of becoming aware of it opens up a complex and challenging itinerary of philosophical exercise, present in the whole Platonic tradition. This paper will examine the various paths designed to facilitate contemplation, as well as the roles of imagination and memory in these processes.